1996
DOI: 10.2343/geochemj.30.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric methane over the North Pacific from 1987 to 1993.

Abstract: Atmospheric methane mixing ratios were measured over the North Pacific during the winter season from 1987 to 1993 to extend our methane record since 1978. The latitudinal distribution of methane mixing ratio showed a north-to-south gradient from mid-latitudes to the equator every year. A sharp mixing ratio gradient often appeared at the boundary between the winter monsoon and the trade wind regions around 20°N. No significant longitudinal gradient was found during the winter season, although methane levels alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Matsueda et al [62] thought a slight change in wind speed could directly affected CH 4 concentration. Zhang et al's research [47] indicated that as the sink of CH 4 and N 2 O, the uncertainty of the value contributed by the ocean was altered by the change of wind speed.…”
Section: Influences Of Sea Surface Temperature and Wind Speed To The mentioning
confidence: 99%
“…Matsueda et al [62] thought a slight change in wind speed could directly affected CH 4 concentration. Zhang et al's research [47] indicated that as the sink of CH 4 and N 2 O, the uncertainty of the value contributed by the ocean was altered by the change of wind speed.…”
Section: Influences Of Sea Surface Temperature and Wind Speed To The mentioning
confidence: 99%
“…Several systematic observational programs have contributed to the documentation of the increasing global abundance of atmospheric methane over this period [e.g., Dlugokencky et al , 2001; Worthy and Ernst , 1999; Mahieu et al , 1997; Matsueda et al , 1996; Aoki et al , 1992; Khalil and Rasmussen , 1990; Brunke et al , 1990; Blake and Rowland , 1988; Fraser et al , 1986]. While there has been an overall increase of 13% in methane abundance between 1978 and 1999, the growth rate has been declining [e.g., Dlugokencky et al , 1998; Matsueda et al , 1996; Khalil and Rasmussen , 1993; Steele et al , 1992], but accompanied by large interannual variations [ Dlugokencky et al , 2001, 1996, 1994a]. Natural processes such as volcanic eruptions seem capable of causing such interannual variations in the global methane growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction is considered to be the principal pathway in which chlorine atoms are removed from the ozone-destroying ClO x cycle . Methane, the most abundant organic species in both the troposphere and the stratosphere, is one of the major greenhouse gases in the atmosphere, and its concentration has steadily increased by about 1% per year for the past 150 years, although this rate has been significantly reduced in the last 5 years . To establish a global methane budget and strengths of various natural and anthropogenic sources of methane is clearly important in order to understand future climate changes.…”
Section: Introductionmentioning
confidence: 99%